(untitled) (Sciental Journal of Education Humanities and Social Sciences, 2025)
This paper explores how interactive technologies digital storytelling, gamified heritage apps, and COIL-like digital exchanges can leverage English folklore to stimulate intercultural dialogue and develop intercultural communicative competence among preschool teacher trainees. Drawing on theoretical models of ICC and empirical work on folklore in ELT, digital storytelling in early childhood, gamification for heritage learning, and COIL-based intercultural projects, the paper proposes a technology-mediated pedagogical approach and reports qualitative outcomes from pilot implementations reported in the literature. The evidence shows increased cultural interest, reflective capacity, and readiness to include diverse cultural perspectives in early childhood practice when folklore is used via interactive technologies.